Thinking and building on shaky ground on architetcure in seismic regions - Fu, Yun (Birkhäuser, 2023)
Building with earthquakes is a familiar yet persistent design problem for resilient construction on all continents. This book elaborates on various factors for earthquake-resilient architecture in six thematic chapters that explore the design strategies of lightness, quickness, exactitude, visibility, multiplicity and consistency. These factors allow designers to develop contextual solutions that marry technical know-how with social and cultural understanding, ranging in scale from buildings to furniture and urban master plans. 120 case studies from roughly 30 countries, including some highly prestigious buildings, provide a comprehensive overview of the different design strategies.
Bibliographie: Seiten 346-347
Keywords: Geschichte 1900-2017; Erdbebensicherheit; Architektur; Bildband; Hochschulschrift